ЎҚУВЧИЛАРДА ХАЛҚ МИЛЛИЙ ҲУНАРМАНДЧИЛИГИ КАСБЛАРИГА ҚИЗИҚИШНИ ШАКЛЛАНТИРИШДА ФАНЛАР ИНТЕГРАЦИЯСИ ИМКОНИЯТЛАРИ - Шомирзаев, М.Х. (SCIENCE and SOCIETY, 2019)
The article deals with the study of scientific-practical and psychological factors of organization of professional orientation in the public educational schools and training in pupils in conscious choosing of profession.
Keywords: professional orientation; psychological regularities; professional motivation; psychological factors; psychological state; cognitive psychological processes